Mindfulness based therapy intervention for reducing stress among students In senior high school during covid19 outbrake - Amalianita, Berru; Ifdil, Ifdil (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2021)
This study aims to analyze the level of stress and the effect of mindfulness based therapy in reducing stress in senior high school students. The subjects in this study were thirteen students in conditions of severe stress. This research method uses single subject research (SSR) with research design A-B-A. In determining the increase in stress, the DASS scale measurement model instrument was used. Furthermore, the data were analyzed with non-parametric statistics using the Wilcoxon signed rank test. The results showed that before being given mindfulness based stress therapy the students were in the heavy category. Then, after treatmen of mindfulness based therapy, the students' stress levels decreased. Based on the results of the wilxocon test, it was also found that there was a decrease in student stress before and after being given mindfulness based therapy. Thus, it can be concluded that mindfulness based therapy is effective in reducing stress levels in students during the Covid19 outbrake